2009
DOI: 10.1136/bmj.b1033
|View full text |Cite
|
Sign up to set email alerts
|

Will doctor rating sites improve the quality of care? No

Abstract: The UK government has signalled its support for rating sites with the decision to set up its own through the NHS Choices website. Neil Bacon (doi:) believes they provide essential feedback for doctors, but Margaret McCartney is concerned that the potential harms are still unclear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 8 publications
2
44
2
2
Order By: Relevance
“…We need to do something similar for the modern generation in health care." 10 In contrast, physician groups in the US have expressed opposition to physician rating websites on the grounds that reviews will be mostly negative. 11 We found that neither of these viewpoints accurately reflects the state of physician rating in the US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We need to do something similar for the modern generation in health care." 10 In contrast, physician groups in the US have expressed opposition to physician rating websites on the grounds that reviews will be mostly negative. 11 We found that neither of these viewpoints accurately reflects the state of physician rating in the US.…”
Section: Discussionmentioning
confidence: 99%
“…The British National Health Service (NHS) has encouraged patients to review their physicians and hospitals, suggesting that this new form of public reporting is growing in popularity and gaining respect. 9,10 In the US, however, physician organizations [including the American Medical Association (AMA)] have opposed the development of physician-rating websites, arguing that the identity of patients cannot be confirmed, physicians' responses will be hampered by confidentiality issues, and reviews will be excessively negative. 11 Despite this controversy, little is known about physician-rating websites.…”
mentioning
confidence: 99%
“…Within the health care community, many have raised concerns about the accuracy of comments expressed on the Web. 13,14 Although ethically viable, it is understood that providing physician-specific ratings based upon publicly available sources remains a controversial position within the profession (and engendered much discussion among the authors). The growing popularity of physician-rating Web sites and the information they place in public view forces the debate forward.…”
Section: Feasibility Of Real Time Satisfaction Surveysmentioning
confidence: 99%
“…[10][11][12] Online sites could also provide venues for families to express views that they might not otherwise feel comfortable sharing. 13 However, the value of these Web sites and the ratings they provide have been questioned on multiple grounds, [14][15][16][17] with criticisms that they lack standardization of rating methods, fail to ensure that ratings include a representative sample of patients for each provider, and have insufficient safeguards against excessively positive comments (eg, physicians' self-promotion) or negative comments (eg, patients' defamatory language).…”
mentioning
confidence: 99%